Anesthetic Management of an Elderly Patient with Dilated Cardiomyopathy and Hypothyroidism for Inter-Trochanteric Fracture - Subedi, Deepika; Aryal, Diptesh; Shrestha, Anil (Journal of Chitwan Medical College, 2019)
Dilated cardiomyopathy is a primary myocardial disease characterized by left ventricular or biventricular dilation and impaired contractility. The anesthetic management of a patient with dilated cardiomyopathy undergoing a non-cardiac surgery is always challenging and may be associated with high mortality. Furthermore, perioperative morbidity becomes more frequent in the elderly with steep increases after the age of 75. We are reporting the successful anaesthetic management of a 93 years old patient with severe dilated cardiomyopathy planned for surgical repair of inter-trochanteric fracture under combined spinal anesthesia.